The Literature of the Colombian Pacific Coast and the Construction of a Cultural Identity. - Arboleda, Carlos (2002)
Keywords: dept.wll; faculty_collection; sabbatical_report

Agítese Bien: A New Look at the Hispanic Avant-Gardes - Pao, María T.; Hernández Rodríguez, Rafael (Juan de la Cuesta, 2002)
Keywords: 20th century; History and criticism; History and criticism; Latin American literature; History and criticism; Literature; Experimental; History and criticism; Spanish American literature; Latin America; Spain; Spanish literature; dept.wll; faculty_collection

The evolving door: providing technology access for post-secondary students in a constantly changing technology-based culture - Hecht, Janice; Zamfir, Bogdan (International Conference on Computers Helping People with Special Needs, 2002)
The Center for Adaptive Technology at Southern Connecticut State University was established in 1988 to provide access to computers for students with disabilities. The challenge of keeping current with both standard and adaptive technology has caused our service to evolve from a focused, centralized model to an integrated model providing technology access to students regardless of their location on campus. © Springer-Verlag Berlin Heidelberg 2002.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Adaptive technology; Artificial intelligence; Centralized models; Computer science; Computers; Integrated modeling; Students; Technology-based; dept.wll

Out of Africa - Feinberg, H.M.; Solodow, J.B. (Journal of African History, 2002)
This article traces the origins of the familiar quotation, 'there is always something new coming out of Africa'. It demonstrates that the phrase was a proverb that originated in Greece no later than the fourth century BC. It charts the transmission of the phrase from Aristotle to the twentieth century, noting that Erasmus is the most important link in the Renaissance and that he may be responsible for the current form in which the phrase is used. The article also shows that the meaning of the phrase was very different in ancient times from what it is today. Whereas 'something new' to Aristotle meant strange hybrid animals, current writers use the phrase with a sense of admiration.
9 citations (Crossref) [2023-10-31]
Keywords: Africa; Historiography; dept.his; dept.wll; history; perception; regional geography